Emergence of two lamellas during impact of compound droplets - Liu, Dongdong (2019)
A compound droplet consisting of water and silicone oil either spreads or splashes upon impacting a solid surface. We show that the transition from spreading to splashing of this type of compound droplet can be changed by varying the volumetric oil ratio in the droplets. In the spreading regime, we observe a surprising emergence of two lamellas spreading one after the other: the first spreading lamella consists of only oil and the trailing one water. We show that the two lamellas eventually meet, significantly affecting the spreading dynamics. Finally, we quantify the maximum spreading radius and show that it is a function of both the impact velocity and the volumetric oil ratio.